Liposome-based gene delivery systems containing a steroid derivative: computational and small angle X-ray diffraction study1. Issue 67 (24th July 2015) - Galeazzi, R.; Bruni, P.; Crucianelli, E.; Laudadio, E.; Marini, M.; Massaccesi, L.; Mobbili, G.; Pisani, M.
<x xml:space="preserve">Abstract</x> The structural properties and the phase behaviour of mixed composition liposomes containing a functionalized lipid are investigated with the aim to design neutral liposomes able to coordinate metals and to complex DNA.